USE OF ACTIVE METHODOLOGIES FOR THE TEACHING OF NEUROANATOMY - Martins Leite Padilha, Cátia; Moreira Salgado Franco, Norma; Rocha Mendonça, André; da Silva Clerc de Freitas, Talita; Vitória de Almeida, Bruna; Cristina Gomes da Silva, Isabel (Health and Society, 2025)
In recent decades, more and more in higher education, active methodologies have been applied, playing a significant role in expanding knowledge. There is a consensus on the perception of the need to use practical tools that contribute positively to learning in neuroanatomy. Therefore, the present work aimed to present tools used in teaching practice based on active methodologies, of which the following stand out: - handout with boards for activities in class, where students identify neuroanatomical structures by colors and legends; - synthetic anatomical parts; 2D and 3D models; made in groups by themes; - sample of neuroanatomy; - group dynamics and pedagogical gymkhana of knowledge and social responsibility. Considering the experiences based on more than twenty years of the teaching staff in the exercise of higher education focused on health and aligned with the instruments for evaluating undergraduate courses at the MEC, it is relevant to define innovation as creative ideas that contribute positively to the quality of teaching and learning process. Finally, the activities demonstrated encouraged critical thinking, problem solving, decision-making and the practical application of the contents studied.